2010
DOI: 10.3233/jad-2010-1252
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin B12 Levels in Alzheimer's Disease: Association with Clinical Features and Cytokine Production

Abstract: Alzheimer's disease (AD) has been associated with up-regulation of pro-inflammatory cytokines (e.g., specific gene variants for TNF-alpha; IL-6; IFN-gamma) and low plasma levels of cyanocobalamin (vitamin B12). Our goal was to relate B12 levels to AD symptoms and to expression of pro-inflammatory cytokines. Clinical manifestations were investigated for a case series of fifty-five outpatients using the MMSE, Neuropsychiatric Inventory (NPI) and Cornell Scale for Depression in Dementia (CDDS). Plasma B12 levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 59 publications
3
22
0
2
Order By: Relevance
“…This meta-analysis also revealed decreased levels of leptin and IL-1 receptor antagonist in AD patients and it is noteworthy that these authors concluded that IL-6 levels were inversely correlated with cognitive scores as ascertained by the MiniMental State Examination (MMSE) [70]. The last finding is unsurprising as there is a large body of evidence confirming that inflammatory signals can have a severe adverse effect on brain function, and is consistent with the work of several research teams which have reported that PIC levels in AD patients are positively associated with cognitive decline, increased frequency and severity of neuropsychiatric symptoms, disease severity and overall disease progression [71][72][73][74][75][76].…”
Section: Evidence Of Peripheral Inflammation In Adsupporting
confidence: 68%
“…This meta-analysis also revealed decreased levels of leptin and IL-1 receptor antagonist in AD patients and it is noteworthy that these authors concluded that IL-6 levels were inversely correlated with cognitive scores as ascertained by the MiniMental State Examination (MMSE) [70]. The last finding is unsurprising as there is a large body of evidence confirming that inflammatory signals can have a severe adverse effect on brain function, and is consistent with the work of several research teams which have reported that PIC levels in AD patients are positively associated with cognitive decline, increased frequency and severity of neuropsychiatric symptoms, disease severity and overall disease progression [71][72][73][74][75][76].…”
Section: Evidence Of Peripheral Inflammation In Adsupporting
confidence: 68%
“…This sample was already reported [24][25][26]. Recruitment setting was the Neuropsychiatric Clinic of the Eginition Hospital in Athens, an academic center for neuropsychiatric disorders.…”
Section: Greek Samplementioning
confidence: 99%
“…A number of pro- and anti-inflammatory markers have been related to neuropsychiatric symptoms and functional level in aging and Alzheimer’s disease including TNFα [31], IL-1 [32, 33], IL-6 [30, 34, 35], IL-7 [36], IL-10 [37], IL-15 [38] and IL-18 [39]. …”
Section: Introductionmentioning
confidence: 99%